Busyness and its impact on speed of work. - Soon, Yi Zhen. (2011)
Talk of busyness is prevalent in today's world. However, busyness is more than time shortage or merely having a lot to do. This study discusses the acceleration of the speed of life and the valuing of “doing more in less time”. Though studies are abound on how factors like clock time, people's pattern of activity consumption, affluence and technology contribute to an accelerated speed of life and in turn make people feel “busy”, little has been done on the inverse relationship. Therefore, this study seeks to find if a busy person will complete a task faster than someone who does not feel busy. Findings indicate that making one feel busy do indeed result in faster task completion.